Assessment of performance boundaries and operability of low specific thrust GUHBPR engines for EIS2025 - Mo, Da; Roumeliotis, Ioannis; Mourouzidis, Christos; Kissoon, Sajal; Liu, Yixiong (American Society of Mechanical Engineers (ASME), 2022)
This paper aims to develop a robust design process by approaching the performance boundaries and evaluating the operability of the pursued geared turbofan engine with low specific thrust for EIS 2025. A two-spool direct-drive turbofan (DDTF) engine of EIS 2000 was improved according to aircraft specifications and technology boundaries in 2025. A series of optimized engines with consecutive fan diameters were established to seek the ideal engine by balancing SFC, weight and mission fuel burn. The fan diameter was proved to be a decisive factor for lowering SFC and energy usage. The cycle design optimization process achieved a thermal efficiency of approximately 52%, and a propulsive efficiency of 79.5%, which is 8.19% increase in propulsive efficiency by enlarging fan diameter from 1.6m to 1.9m. Meanwhile, the 1.9m-fan diameter engine achieved a reduction in SFC and fuel burn of 7.47% and 6.58% respectively which offers an overall reduction of 30.82% in block fuel burnt and CO2 emission compared to the DDTF engine. A feasibility check verified the viability of the designed optimum engine in terms of fan tip speed, stage loading and AN2. Dynamic simulation offered a deep understanding of transient behaviour and fundamental mechanism of the geared turbofan engine. An important aspect of this paper is the use of advanced CMC materials, which led to an improvement of 4.92% in block fuel burn and 2.93% in engine weight.